Design of Low V-pi High-Speed GaAs Travelling-Wave Electrooptic Phase Modulators Using an n-i-p-n Structure - DONEGAN, JOHN (My University, 2008)
GaAs-based electrooptic phase modulators using an n-i-p-n structure and coplanar waveguide traveling-wave electrodes are designed using the compact 2-D finite-difference time-domain technique and Pade approximation transform. By optimization, an electrical 3-dB bandwidth of 40 GHz and a 6.6-V are predicted for a 5-mm-long modulator.
PUBLISHED
Keywords: Electrooptic modulator, Pade approximation transform, 2-D finite-difference time-domain (FDTD) method, traveling-wave (TW) electrodes.